2012
DOI: 10.1123/tsp.26.3.341
|View full text |Cite
|
Sign up to set email alerts
|

Moral Atmosphere and Masculine Norms in American College Football

Abstract: This study examined on-field antisocial sports behaviors among 274 American football players in the United States. Results indicated that moral atmosphere (i.e., teammate, coach influence) and conformity to masculine norms were significantly related to participants' moral behavior on the field (i.e., intimidate, risk injury, cheat, intentionally injure opponents). In other words, the perception that coaches and teammates condone on-field antisocial behaviors-in addition to conforming to societal expectations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
5
1
Order By: Relevance
“…These traits align with norms of traditional masculinity (e.g., Violence) that are often associated with the “dark side of masculinity” (e.g., Brooks & Silverstein, 1995; Mahalik et al, 2005). Although sports are conceptualized as “masculinized” endeavors (e.g., Richman & Shaffer, 2000) where incidents of on-field violence and antisocial sports behaviors occur (e.g., Shields & Bredemeier, 2007; Steinfeldt, Rutkowski, Orr, & Steinfeldt, 2011), the results of this current study did not identify a significant relationship between the drive for muscularity and conformity to these particular masculine norms (i.e., Winning, Violence, Risk-Taking). Subsequently, future research is needed to better identify not only how masculinity socialization processes operate within sport, but also to examine if conformity to these norms influences participants' desire to be muscular.…”
Section: Discussioncontrasting
confidence: 69%
“…These traits align with norms of traditional masculinity (e.g., Violence) that are often associated with the “dark side of masculinity” (e.g., Brooks & Silverstein, 1995; Mahalik et al, 2005). Although sports are conceptualized as “masculinized” endeavors (e.g., Richman & Shaffer, 2000) where incidents of on-field violence and antisocial sports behaviors occur (e.g., Shields & Bredemeier, 2007; Steinfeldt, Rutkowski, Orr, & Steinfeldt, 2011), the results of this current study did not identify a significant relationship between the drive for muscularity and conformity to these particular masculine norms (i.e., Winning, Violence, Risk-Taking). Subsequently, future research is needed to better identify not only how masculinity socialization processes operate within sport, but also to examine if conformity to these norms influences participants' desire to be muscular.…”
Section: Discussioncontrasting
confidence: 69%
“…Steinfeldt, Rutkowski, Orr, and Steinfeldt (2012) suggested that social gender norms influence acceptable behavior for both men and women. They argue that such norms "guide and constrain men's and women's understanding of how they are supposed to think, feel, and act in society.…”
Section: Sport and Coaching Subculturementioning
confidence: 98%
“…Because men are in so many influential positions in athletics, it is likely that these gender norms are passed down from coach to player. Steinfeldt et al (2012) explained that "sport is an influential environment wherein boys learn values and behaviors (e.g., competi tion, toughness, independence) that are considered to be valued aspects of masculinity within American society" (p. 343). In fact, sport studies literature suggests that many men are turning to sport as a way to fulfill father ing responsibilities (e.g., Kay, 2009;Messner, 2009).…”
Section: Sport and Coaching Subculturementioning
confidence: 99%
“…The authors found that football players who reported “lower levels of adherence to the masculine norm of emotional control and who perceived [hypothetical football player's] crying behavior as appropriate reported higher levels of self-esteem” (Wong, Steinfeldt, LaFollette, et al, 2010, p. 10). Additionally, Steinfeldt, Rutkowski, Orr, and Steinfeldt (2011) examined the relationship between masculine norms and on-field moral functioning among college football players. The authors found that in addition to moral atmosphere (i.e., the influence of coaches and teammates), greater conformity to masculine norms predicted higher levels of antisocial behaviors (e.g., intimidation, risking injury to opponent, cheating, intentionally injuring opponent) on the field of play.…”
Section: Social Norms Theory and Conformity To Masculine Norms Modelmentioning
confidence: 99%